The Influence of Financial Literacy and Income on The Financial Welfare of TNI AD Soldiers in The Waytuba Lampung Air Force Work Unit - Yufiantorais, Syaifullah; Colline, Fredella (Finance and Business Management Journal, 2025)
This study examines the influence of financial literacy and income on the financial well-being of Army Aviation (PENERBAD) soldiers stationed in Way Tuba, Lampung. The main issue addressed in this study is the limited financial management knowledge among soldiers, which potentially affects their ability to plan and maintain a stable financial condition. This study aims to analyze how financial literacy and income levels contribute to soldiers' financial well-being, considering their unique duties and challenges. Using a quantitative method with a primary data approach, data were collected through questionnaires from 75 respondents and analyzed using multiple linear regression with SmartPLS. The findings indicate that financial literacy and income have a positive and significant impact on soldiers' financial well-being. These results highlight the importance of providing ongoing financial education and income management support to improve soldiers' financial resilience. This research also serves as a reference for military leaders in developing policies to strengthen soldiers' financial stability and prevent financial problems such as online gambling and illegal loans. This research contributes to understanding the strategic role of financial literacy in supporting soldier well-being and readiness.